A ética e a confiança nas organizações: um estudo descritivo junto a profissionais da Grande São Paulo - Ramacciotti, Claudio (2008)
The theme´s interest was motivated by the debate about ethical questions in all organization’s activity area, and the attention given to trust in organizational contexts. This work has as an objective to check if in a relation among people supported for ethics and trust improves the employee´s performance in the company. It presents a fundamental bibliographic review about ethics and trust, aiming to give a sustainability theorical contribution. It offers a concept’s view based in the organization: professional ethics, organizational ethics, the ethical company, code of practice, organizational culture and ethics background, the importance of trust and the cognitive trust, as well as a general prospect between the difference, the concept and the history of ethics and moral. In this work, positive and negative aspects that ethics and trust create to the organizations are mentioned. Some discussions were elaborated trying to extend the traditional concepts inside the organizations. To study the thesis central hypothesis, that is to check if the existence of ethics and trust among people promotes an adequate organizational environment, resulting in an improvement of employee´s performance,the theorical reference offered a direction in the questions elaboration. It was made a research with professionals that work in Grande São Paulo´s enterprises. It was stipulated patterns scores, in which the results were submitted and analysed. These results suggests that the people who answered this research believe, in a moderated way, that the existence of ethics and trust among coworkers, results in an improvement of employee’s performance.I must emphasize the mentioned authors affirmations, the contributions that ethics and trust bring to the organizations. The thesis still points the study’s limitations, and suggests ways to be explored by new researches in this field.